Fake Healing Claims for HIV and Aids in Malawi : Traditional, Christian and Scientific - Fiedler, Klaus, Dr (Mzuni texts, 2017)
In this book Klaus Fiedler offers a candid critique of religious faith healing claims - a critique that extents to the Voluntary Male Medical Circumcision Campaign (VMMCC). The book reveals the lack of substantive evidence to back such healing claims and the contradiction between the VMMCC claims and the consequences of those claims in sexual health and practice.